Answer :

Answer:y=7  x=14   z=-5

Step-by-step explanation:

For the equation, we need to use the substitution method. So first we will use the y+2z=-3 and subtract 2z from both side and get y=-3-2z. then we will substitute the y in the 2+y+3z=-6 with y=-3-2z so it will be 2+(-3-2z)+3z=-6. then we combine the like-term so it will be -1+z=-6 then add both side with 1 and get z=-5. substitute the z in the y+2z=-3 with -5 and get y-10=-3 then add 10 to both side to get y=7 then substitute the y in the x-2y+z=-5 with 7 and z with -5 so the equation will be x-19=-5 then add the 19 on both side to get x=14.

Other Questions